Adult Acne Versus Adolescent Acne: A Retrospective Study of 1,167 Patients - Skroza, Nevena (J Clin Aesthet Dermatol, 2018)
Background: Acne is predominantly known as a skin disorder of the adolescent population. However, current research indicates that the prevalence of adult patients with acne, especially among women, is increasing. Objective: The objective of this study was to evaluate differences between adults and teenagers with regard to acne prevalence, patient sex, acne severity, and quality of life. In adult patients, we considered differences in family history of acne, onset, and smoking habits. Design: We performed a retrospective study of a total of 1,167 patients with acne who attended our outpatient clinic from January 2008 to March 2015. Participants: The study population was divided into two groups: adolescent acne and adult acne. Among the adult subjects, 385 were female and 69 were male; among the adolescent subjects, 378 were female and 335 were male. Measurements: The severity of acne was recorded using the Global Acne Grading System. The impact of acne on quality of life was investigated using the Assessment of Quality of Life questionnaire. Results: Study results show that acne in female patients was more prevalent than in male patients. The evaluation of acne severity showed that “mild acne” is the most frequent form. With regard to smoking habits, time of onset, and family history of acne, we did not find any statistically significant differences between the sexes. Conclusion: In both sexes, there are some differences in adult acne versus the adolescent form. Treating adult acne demands a different approach to diagnosis and a tailored management plan that considers all of the variables involved.